Pengaruh Good Corporate Governance,Corporate Social Responsbility Terhadap Kinerja Keuangan Pada Perusahaan Bumn Yang Terdaftar Di Bursa Efek Indonesia Tahun 2020-2022 - Felia Mulyani; Ratnawati Raflis (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This research aims to examine the influence of good corporate governance and Corporate Social Responsibility on financial performance companies listed on the Indonesian Stock Exchange 2020-2022. This research uses a quantitative descriptive approach.The data used is secondary data from the annual reports of state-owned companies listed on the Indonesian Stock Exchange. The sampling technique in this research uses non-profability sampling and the method used is the purposive sampling method. The sample in this research is 11 state-owned companies.The research results show that partially managerial ownership has a significant effect on financial performance and the board of directors has a significant effect on financial performance, while Corporate Social Responsibility has a significant effect on financial performance.